Multi-Product Offshoring - Carsten Eckel; Michael Irlacher (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
In this paper, we incorporate offshoring of labor-intensive goods in a model with multi-product firms, and explore its implications in partial and general oligopolistic equilibrium. We identify important aspects of this phenomenon and argue that improvements in offshoring opportunities can affect the geographic organization of a firm and its product range. Multi-product firms internalize supply linkages (flexible manufacturing) and demand linkages (cannibalization effect). In partial equilibrium, we find that more products are produced offshore on a larger scale and firms expand their product range with better prospects for offshoring. We identify the cannibalization effect as an important transmission mechanism within multi-product firms and show that the latter effect hits domestic labor demand in addition to the well-known relocation effect. Interestingly in general equilibrium these effects lead to adjustments in domestic factor prices and may cause a partial re-relocation of product lines.
urn:nbn:de:bvb:19-epub-21021-1
Keywords: F12; F23; L23; 330; Multi-Product Firms; Cannibalization Effect; Product Range; Efficiency-seeking Offshoring; General Oligopolistic Equilibrium.